Study of Aging Mechanisms for Structural Materials within SAFELIFE Project - Sevini, F.; Debarberis, L.; Taylor, N.; Gerard, R.; Brumovsky, M. (Проблемы прочности, 2004)
EUROATOM research programs aimed at study of aging mechanisms and remedial procedures for structural materials of nuclear reactor components have been analyzed. Within this framework, projects are carried out focusing on the development of non-destructive techniques applied to thermal aging, neutron embrittlement monitoring, improved surveillance for WWER-440 reactors, dosimetry, and advance fracture mechanisms for NPP integrity assessment. Among major achievements are the ATHENA project activities on re-embrittlement model validation after annealing and the effect of chemical composition on embrittlement rate in RPV steels. A brief description is given of the main results of current EUROATOM projects, as well as the next research stage goals of a more expanded SAFELIFE network.